Coexistence Of Biofilm Formation And Antibiotic Resistance Profile Of Uropathogenic E. Coli (Upec) (Journal of Pharmaceutical Negative Results, 2022)
The bacteria known as Uropathogenic Escherichia coli (UPECs) play a major role in triggering UTIs (UTIs). Antibiotic resistanceamong UPEC strains may progress faster if UTIs in Anbar continue to be treated with beta-lactam antibiotics without antibioticsusceptibility testing. In a study evaluating cephalosporin-resistance among 141 E. coli clinical isolates, 100 were found in urinesamples. Antibiotic resistance was analyzed using the VITEK-2 system. The results indicated that resistant to most β-lactamases usedin this study was associated with biofilm formation. 88.5% of UPEC isolates that showed biofilm positive were resist to 3rd generationcephalosporins with a statistically highly significance (P=<0.0001).